The role of betting on digital credit repayment, coping mechanisms and welfare outcomes: Evidence from Kenya - Richard Chamboko; Sevias Guvuriro (International Journal of Financial Studies, 2021)
Digital financial services and more importantly, mobile money, have become an important financial innovation to advance financial inclusion in developing and emerging economies. While digital financial services have improved the lives of many Kenyans, to the growing betting segment of the Kenyan population, these innovations have also brought great convenience to betting. The innovations have allowed easy access to digital credit which can be used for betting. Despite betting or gambling being a widely studied area, particularly in developed countries, little is known about its interaction with financial innovations such as digital financial services in developing and emerging economies. Using data from a 2017 digital credit survey in Kenya, this study investigates if bettors are more likely than non-bettors to be financially distressed or engage in welfare-undermining coping strategies and potentially experience inferior welfare outcomes. The study uses a representative sample of 1040 digital borrowers, of which 304 were digital bettors. Using multivariate logistic regressions, the study found that, after controlling for socio-economic and demographic factors, bettors are significantly more likely than non-bettors to be financially distressed, engage in welfare undermining coping strategies, and have inferior welfare outcomes.
Keywords: D60; E42; E51; G23; G29; O12; O33; 330; betting; coping strategies; digital credit; digital financial services; financial distress; welfare outcomes